The Influence of Demographic Factors and Psychological Factors of Fertile Age Women (WUS) on Cervical Cancer Screening Acetic Acid Visual Inspection Method (IVA) in the Work Area of Puskesmas Sitinjo, Dairi Regency, 2016 - Perak M A Hutagalung; Herlina Evi Yanti Manik (Institute of Computer Science (IOCS), 2021)
Data from Puskesmas Sitinjo that in 2015 the number of goals WUS many as 2,257 and target of 600 only 181 (30%) WUS who checked himself participated in the screening program (early detection) method of IVA cervical cancer. Factors that are supposed to influence the screening measures that are demographic factors (age, education, income, occupation, marital status) and psychological factors (perception, attitude, and motivation). This research is analytic survey with cross-sectional approach. The study was conducted in Puskesmas Sitinjo. The study was conducted in April-July 2016. The population of as many as 2257 people, while a sample of 291 people. Data analysis was performed using univariate, bivariate analysis using chi-square test, and multivariate logistic regression test double. Based on the results of the study showed that demographic factors (education, p = 0.002; work, p = 0.000) and psychological factors (perception, p = 0.000; attitude, p = 0.001; and motivation, p = 0.000) significantly influence the actions cervical cancer screening the method IVA in Puskesmas Sitinjo Dairi 2016. Variables that no effect is age (0.895), income (0.128), marital status (p = ). The variables that most influence the actions of cervical cancer screening method IVA is motivation. Mothers with good motivation to have a tendency to take action cervical cancer screening method IVA 23.8 times higher than those whose mothers lack motivation. PHC Chief Sitinjo suggested to disseminate information to the public, especially the EFA mothers who have been sexually active through health education, distribution of brochures, leaflets,